2015
DOI: 10.1177/0960327115583361
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of cholinergic and oxidative stress biomarkers in brains of diabetic and hypercholesterolemic rats

Abstract: Objective: Diabetes mellitus (DM) and hypercholesterolemia (HC) when poorly controlled lead to debilitating central nervous system complications including cognitive deficits and memory impairment. In the present study, we investigated the mechanisms that may be responsible for such deficits. Methods: Both diabetes and HC were induced in two groups of rats independently using alloxan and high cholesterol di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…On the occasion of memory impairment, an important parameter to be evaluated is the activity of AChE. This enzyme regulates the concentration of the neurotransmitter acetylcholine, being involved in memory and learning processes, as well as sensitivity and responsiveness to CNS disorders (Hegazy et al, 2016). We found that the AChE activity in the cortex did not significantly differ among the groups, in agreement with previous results with hyperlipidemic rats from our laboratory (Ruchel et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…On the occasion of memory impairment, an important parameter to be evaluated is the activity of AChE. This enzyme regulates the concentration of the neurotransmitter acetylcholine, being involved in memory and learning processes, as well as sensitivity and responsiveness to CNS disorders (Hegazy et al, 2016). We found that the AChE activity in the cortex did not significantly differ among the groups, in agreement with previous results with hyperlipidemic rats from our laboratory (Ruchel et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism of increased ChE activity in diabetic patients is not fully clear at present. Usually, diabetic patients have high oxidative stress indices in the blood which might be accompanied with cholinergic dysfunction 1,[33][34][35] It is possible; therefore, that oxidative stress status in the patients is the contributing factor to such an enzymatic change. Correspondingly, experimentally induced oxidative stress in 2-week old chicks was found to increase the susceptibility of the animals to organophosphate poisoning, which acts primarily to inhibit cholinesterases in the neuronal tissues, neuromuscular junctions as well in the plasma and erythrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…18 Further evidences in rats suggest a modulatory role of oxidative stress on ChE activity. 35 Induction of free oxygen radicals can increase the toxicity of pesticides including the organophosphates. 36 Erythrocyte membranes are sensitive to oxidative damage due to their high polyunsaturated fatty acid content as well as high oxygen and hemoglobin concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…ACh is a neurotransmitter that is synthesized by choline actyltransferase and hydrolyzed by AChE and it plays a major role in learning and memory in the brain. AD is known to exert excessive activation of AChE and thereby inhibit the role of cholinergic neurotransmitters, thus affecting cognition, and furthermore affecting neuronal apoptosis [29]. IR mainly breaks down energy homeostasis by mitochondrial dysfunction and impairs the role of insulin, which is known to regulate the neurotransmitters ACh and norepinephrine, affecting cognition [25].…”
Section: Discussionmentioning
confidence: 99%